Individual placement and support (IPS) for patients with offending histories: the IPSOH feasibility cluster randomised trial protocol - Khalifa, Najat; Talbot, E.; Schneider, Justine M.; Walker, D.M.; Bates, P.; Bird, Y.; Davies, D.; Brookes, C.; Hall, J.; Völlm, Birgit (BMJ Publishing Group, 2016)
Introduction: People with involvement in forensic psychiatric services face many obstacles to employment, arising from their offending, as well as their mental health problems. This study aims to assess the feasibility of conducting a randomised controlled trial (RCT) to evaluate the effectiveness of individual placement and support (IPS), in improving employment rates and associated psychosocial outcomes in forensic psychiatric populations. IPS has been found consistently to achieve employment rates above 50% in psychiatric patients without a history of involvement in criminal justice services. Methods/design: This is a single-centre feasibility cluster RCT. Clusters will be defined according to clinical services in the community forensic services of Nottinghamshire Healthcare NHS Foundation Trust (NHCT). IPS will be implemented into 2 of the randomly assigned intervention clusters in the community forensic services of NHCT. A feasibility cluster RCT will estimate the parameters required to design a full RCT. The primary outcome is the proportion of people in open employment at 12- month follow-up. Secondary outcome measures will include employment, educational activities, psychosocial and economic outcomes, as well as reoffending rates. Outcome measures will be recorded at baseline, 6 months and 12 months. In accordance with the UK Medical Research Council guidelines on the evaluation of complex interventions, a process evaluation will be carried out; qualitative interviews with patients and staff will explore general views of IPS as well as barriers and facilitators to implementation. Fidelity reviews will assess the extent to which the services follow the principles of IPS prior, during and at the end of the trial.